The relation between specific motor skills and daily living skills in autistic children and adolescents - Skaletski, Emily C.; Cardona, Sailery Cortes; Travers, Brittany G. (Frontiers in Integrative Neuroscience, 2024)
Introduction Motor skill difficulties are common in autistic children and are related to daily living skills (DLS). However, it remains unclear which specific motor tasks are most likely to impact overall DLS. This study sought to fill this gap. Methods and results In 90 autistic children and adolescents (ages 6–17 years), we found that fine/manual motor tasks, like drawing or folding, demonstrated significant medium-sized relations with DLS, even after accounting for IQ and sensory features, whereas tasks in the areas of bilateral coordination, upper-limb coordination, and balance only related to DLS (small effect sizes) prior to accounting for IQ and sensory features. When looking at an overall balance score, we found that IQ significantly interacted on the relation between overall balance and DLS. Discussion These results further demonstrate the particular importance of fine/manual motor skills for DLS in autistic youth, even when accounting for IQ and sensory features. Indeed, accounting for sensory features strengthened the relations between fine/manual motor skills and DLS. Our findings provide evidence of the impact of cognitive factors on the relation between balance and DLS, indicating that it may be that autistic individuals with lower IQs experience relations between balance and DLS that are different than their peers with higher IQs. Our findings support the benefit of considering individual motor skills rather than domain-level information when assessing ways to promote DLS in autistic youth. The results further shed light on the importance of fine motor skills, as well as the unique relationship of balance and DLS in autistic individuals with lower IQs.